The Importance of Religious Moderation in Strengthening Interfaith Brotherhood in Multicultural Societies - Syaban Abdul Karim (Spiritus: Religious Studies and Education Journal, 2025)
The importance of religious moderation in strengthening interfaith brotherhood in multicultural societies is an increasingly relevant issue in the midst of increasingly plural social life. The diversity of religions, cultures, and ethnicities in Indonesia often poses challenges in building harmonious relationships between various groups. Religious moderation, as an approach that promotes moderation, tolerance, and mutual respect between religious communities, is an important key in maintaining such harmony. The purpose of this research is to analyse the role of religious moderation in strengthening interfaith brotherhood in a pluralistic society. The method used in this research is a literature study with a qualitative approach, collecting data from various relevant sources, such as articles, books, and previous research results. The results of the discussion show that religious moderation plays a significant role in creating space for interfaith dialogue, reducing conflict, and increasing awareness of the importance of tolerance and respect for differences. Religious moderation education in schools and communities has also proven effective in shaping a more open and peaceful mindset. Religious moderation is not only the teaching of tolerance, but also the application of religious values that emphasise compassion and peace. Therefore, religious moderation is an important strategy in strengthening interfaith brotherhood in Indonesia.